Comments on “Human Body Shadowing in Cellular Device-to-Device Communications: Channel Modeling Using the Shadowed κ−μ Fading Model” - Moreno-Pozas, Laureano; López-Martínez, Francisco Javier; Cotton, Simon L.; París-Ángel, José Francisco; Martos-Naya, Eduardo (Institute of Electrical and Electronics Engineers, 2017)
We provide some comments and subsequent corrections to a paper recently published in this Journal (see ibid., vol. 33, no. 1, pp. 111-119, Jan. 2015). More precisely, we show that the pdf for the κ-μ shadowed fading model given by S.L. Cotton cannot be obtained from the underlying statistical model proposed therein. To support this observation, we present a detailed mathematical analysis as well as some Monte Carlo simulations. We also demonstrate that by simply adopting the underlying statistical model for the κ-μ shadowed fading distribution proposed in an earlier and independent work by J.F. Paris enables the κ-μ shadowed pdf later presented by S.L. Cotton to be obtained.
Keywords: Modelos matemáticos; Análisis matemático; Fading channels , Mathematical model , Land mobile radio cellular systems , Monte Carlo methods , Mathematical analysis; Fading channels; Mathematical model; Land mobile radio cellular systems; Monte Carlo methods; Mathematical analysis